2022
DOI: 10.1007/s10668-022-02507-z
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown impact on energy consumption in university building

Abstract: COVID-19 has had a significant impact on the global demand and consumption of energy. In particular, the effect of the lockdown measures due to the COVID-19 pandemic can be seen directly in the reduced energy consumption in educational buildings. Therefore, the objective of this study is to assess the impact of COVID-19 on the electricity use in university buildings. The Research Complex Building of the National University of Malaysia was selected as a case study. An energy audit analysis was conducted based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The temporary closure and restrictions of oncampus activities led to significant changes in electricity consumption. It is important to note that, a substantial reduction, for the semi-COVID-19 academic year at 20.92% and the COVID-19 academic year at 35.50%, was found in this study when compared to the National University of Malaysia [36], University of Almeria [32], Griffith University [33], and Universitat Politècnica de Catalunya [37], as 11%, 15%, 16%, and 19%, respectively. This can be attributed to specific contextual factors such as lockdown restriction levels, building characteristics, facility management, HVAC systems, and climate conditions, which need to be interpreted cautiously.…”
Section: Academic Year Comparison Analysismentioning
confidence: 50%
See 2 more Smart Citations
“…The temporary closure and restrictions of oncampus activities led to significant changes in electricity consumption. It is important to note that, a substantial reduction, for the semi-COVID-19 academic year at 20.92% and the COVID-19 academic year at 35.50%, was found in this study when compared to the National University of Malaysia [36], University of Almeria [32], Griffith University [33], and Universitat Politècnica de Catalunya [37], as 11%, 15%, 16%, and 19%, respectively. This can be attributed to specific contextual factors such as lockdown restriction levels, building characteristics, facility management, HVAC systems, and climate conditions, which need to be interpreted cautiously.…”
Section: Academic Year Comparison Analysismentioning
confidence: 50%
“…Similar to previous studies [32][33][34][35][36][37][38][39][40], to analyze changes under the temporary closure, a comparative analysis was done by the process of comparing data from three academic years, and distinguishing the similarities and differences in electricity usage patterns. In this study, data from three academic years were displayed and analyzed including:…”
Section: Academic Year Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Paula Brumer Franceschini evaluated the existing research methods of campus building performance, and looked forward to the future research topics based on the impact of the new crown epidemic on campus personnel living behavior models [38] . Sharifah Nurain Syed Nasir et al compared the building electricity consumption of a research complex at the National University of Malaysia in 2019-2020 and found that the building's energy consumption decreased by 11% during the covid-19 period [39] . In contrast, Reza Mokhtari et al used a simulation optimization algorithm to evaluate the effects of the presence of people, air exchange rate, class time and work time on HVAC system energy consumption and the number of people infected with New Crown Pneumonia in a building at Tehran University during the New Crown Pneumonia epidemic, concluding that increasing the ventilation rate of the building during the New Crown Pneumonia epidemic was effective in reducing the number of infections, but the corresponding building energy consumption would also increase [40] .…”
Section: Introductionmentioning
confidence: 99%
“…As part of the energy audit analysis, lighting audit findings also have been discussed in [12] where lighting contributes 10% of the overall energy saving. Other energy audit work in the academic building was fulfilled by [13] where they analyzed the impact of the pandemic on energy consumption and realized more energy conservation measures could be implemented during the endemic period.…”
Section: Introductionmentioning
confidence: 99%